Hormesis in Pathogenic and Biocontrol Fungi: From Inhibition to Stimulation - Krisnanda Surya Dharma; Suryanti Suryanti; Ani Widiastuti (Universitas Sebelas Maret, 2024)
Hormesis, a biphasic response where low doses of stressors stimulate growth and high doses inhibit it, has significant implications for agricultural chemical use. This review explores the impact of low-dose fungicides or pesticides on pathogenic and biocontrol fungi. This study highlights how sublethal dose exposure can enhance growth and virulence of fungal pathogens, while also potentially increasing their stress tolerance at higher doses. This phenomenon complicates fungicide resistance management strategies. The review focuses on specific fungicides such as dimethachlone, prochloraz, carbendazim, and others, and their hormetic effects on fungal pathogens. Furthermore, the effects of low-dose pesticides and fungicides on beneficial fungi like entomopathogenic and arbuscular mycorrhizal fungi (AMF) are discussed. Here, low-dose exposure can stimulate the germination of entomopathogenic fungal conidia and enhance AMF root colonization and phosphorus uptake. However, hormesis can have trade-offs, potentially leading to unforeseen consequences for the organism. A thorough understanding of hormesis and dose-dependent fungicide effects is crucial for optimizing disease management and agricultural practices. This knowledge can inform strategies to minimize pathogen resistance and promote sustainable approaches. Implementing integrated disease management that combines fungicides with different modes of action alongside other control methods can be effective. Careful consideration of fungicide doses and potential hormesis effects is paramount for ensuring sustainable plant disease control and food security.